Schizandrin A Inhibits Microglia-Mediated Neuroninflammation through Inhibiting TRAF6-NF-κB and Jak2-Stat3 Signaling Pathways - Song, Fangjiao; Zeng, Kewu; Liao, Lixi; Yu, Qian; Tu, Pengfei; Wang, Xuemei (PLOS ONE, 2016)
Microglial-mediated neuroinflammation has been established as playing a vital role in pathogenesis of neurodegenerative disorders. Thus, rational regulation of microglia functions to inhibit inflammation injury may be a logical and promising approach to neurodegenerative disease therapy. The purposes of the present study were to explore the neuroprotective effects and potential molecular mechanism of Schizandrin A (Sch A), a lignin compound isolated from Schisandra chinesnesis. Our observations showed that Sch A could significantly down-regulate the increased production of nitric oxide (NO), tumor necrosis factor (TNF)-α and interleukin (IL)-6 induced by lipopolysaccharide (LPS) both in BV-2 cells and primary microglia cells. Moreover, Sch A exerted obvious neuroprotective effects against inflammatory injury in neurons when exposed to microglia-conditioned medium. Investigations of the mechanism showed the anti-inflammatory effect of Sch A involved the inhibition of inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX-2) expression levels and inhibition of the LPS-induced TRAF6-IKKβ-NF-κB pathway. Furthermore, inhibition of Jak2-Stat3 pathway activation and Stat3 nuclear translocation also was observed. In conclusion, SchA can exert anti-inflammatory and neuroprotective effects by alleviating microglia-mediated neuroinflammation injury through inhibiting the TRAF6-IKKβ-NF-κB and Jak2-Stat3 signaling pathways.